Social Responsibility in Banking Sector: Evidence from Europe - José Tiago Gonçalves de Sousa (2020)
The environment, the humanitarian causes, the equality in its various senses and the other issues of social importance are themes that have awakened, pointing as a priority in the future (and in the present). In companies, this can be translated into Social Responsibility. And among all sectors, the banking sector has stood out. Responsibility in the Banking Sector is a topic of growing interest and whose study lacks a more methodological basis. Banks depend on the trust of society and can change social behavior through their activity criteria. This dissertation contributes to the clarification of the concepts and quantitatively accesses the potential financial impact of the Social Responsibility on the profitability of the banks. The results of this study suggest that Social Responsibility does not harm the financial profitability of most banks. However, it suggests that impact is significantly different between large banks and small banks as, ceteris paribus, a Social Responsibility improves the financial profitability of larger banks.